Exploring religious pluralism: Refining the defining - Ibrahim, Haslina (Fakulti Kepimpinan & Pengurusan, USIM, 2018)
In 1985 John Hick (1922 –2012) introduced the philosophy of religious pluralism in providing a solution to theological conflict of salvation and the religious conflicting truth-claim that in his impression, hampering religious coexistence. Salvation, he criticized, is the root of exclusivism and a transformation from within religion is needed to rid of it. Hickean pluralism has received support, rejection and adaptation from scholars, activists and leaders of diverse religions until present day. Six years later, Diana L. Eck started the Pluralism Project focussing on the diverse religious contour in the United States in keeping with the American liberal democratic way of life and the notion of civil religion. Eck’s version of pluralism has been receiving wider acceptance in terms of its definition and operation. Today, after more than thirty years since its inception, the philosophy continues to invite debates on its definition, meaning and practises. This paper therefore, hopes to explore the debates and to share some insights in view of both, Hick’s and Eck’s foundational role. In the quest of refining its meaning, the author will also argue whether religious pluralism and religious plurality are two faces of the same coin. The paper concludes that an evolution of meaning is indispensable in any given term and it will continue to take place. Nevertheless, the context from which religious pluralism emerged is foundational to its conceptualization and philosophical elucidation. Hence, refinement of religious pluralism needs to consider its original context.